Pengaruh Penerapan Latihan Gerakan Rom (Range Of Motion) Terhadap Kekuatan Otot Pasien Pasca Stroke Iskemik - Sri Kurnia Dewi; Lutiyah Lutiyah (Malahayati Nursing Journal, 2022)
ABSTRACT : THE EFFECT OF APPLICATION ROM (RANGE OF MOTION) MOVEMENT EXERCISES ON THE MUSCLE STRENGTH OF POST ISCHEMIC STROKE PATIENS  Intoduction : Range of Motion Exercise in an exercise performed to evaluate and improve the function of the musculoskeletal system and is olso one of therapy in stroke patients that aims to increase cerebral blood flow, minimiza disability caused by stroke, so as to refine sensory motoric function.Purpose : the purpose of this resea is to identify the effect of Range of Motion Exercise to the muscle strength of iskemic stroke patients in Neuroligy Department of General Hospital RSUD Cimacan. Method : This study is aquasi experiment with methods Nonequivalent Control Group Design.The sampling technique that used is purposive sampling. Primary data gain from patient observation sheets and secondary data from the medical records of patiennt treated at Neurology Departement og General Hospital RSUD Cimacan. Sampel:this study involving 15 respondents in the research period  Oktober, 2021 – February 2022 and was carried out in the room Neuro RSUD Cimacan. Results :the analysis by using a Paired Sampel T test statistic-Test with significance level (α) 0.05, shows scores and muscle strength before and after done the exersice range of motion have elevated the score avarage of 3.87.The influence of practice range of motion of muscle strength in patients with stroke value of P = 0.003. Conclution :The conclusion that can be drawn from this study is that there in an affect of range of motion exercise on muscle strength in stroke patients in the neurology room of RSUD Cimacan. Keywords: Stroke, ROM and Muscle of Power      INTISARI:PENGARUH PENERAPAN LATIHAN GERAKAN ROM (RANGE OF MOTION)TERHADAP KEKUATAN OTOT PASIEN PASKA STROKE ISKEMIK  Latar Belakang: Latihan Range Of Motiom merupakan kegiatan Latihan yang dapat menentukan nilai dan mengetahui peningkatan fungsi sistem musculoskeletal dan bisa juga menjadi bagian dari terapu lanjutan penderita stroke yang dapat meningkatkan aliran darah otak, serta mengurangi kondisi cacat, dan mampu mengembalikan fungsi sensori motorik.Tujuan: Tujuan dari penelitian ini adalah mengidentifikasi pengaruh Latihan Range Of Motion terhadap kekuatan otot pasien paska stroke iskemik.Metode: Metode yang digunakan yaitu quasi eksperimen dan nenoguivalent control group desain. Sampling menggunakan Surposive sumpling. Data primer didapat dari lembar hasil observasi pasien dan data sekunder didapat dari rekam medis pasien yang dirawat yang dirawat di ruang neurologi RSUD Cimacan. Sample dalam penelitian ini melibatkan 15 responden dengan rentang waktu antara bulan oktober 2021 –  Februari 2022 dan dilakukan di ruang neurologi RSUD Cimacan.Hasil: Analisa dengan menggunakan uji statistic Paired sample T-Test dengan tingkat kemaknaan (α) 0.05, menunjukan kekuatan otot sebelum dan sesudah dilakukan Latihan Range Of Motion mengalami peningkatan score rata-rata 3.87.Kesimpulan : Kesimpulan yang dapat ditarik dari penelitian ini ialah ada pengaruh latihan range of motion terhadap kekuatan otot pada pasien stroke di ruang neurologi RSUD Cimacan. Kata Kunci: Stroke, ROM dan Kekuatan Otot